A Feasibility Study of Biogas Technology to Solving Peri-urban Sanitation Problems in Developing Countries. A Case for Harare, Zimbabwe - G Sibanda; D Musademba; H.C. Chihobo; L Zanamwe (International Journal of Renewable Energy Development, 2013)
This study investigated the feasibility of converting organic waste into energy using biogas technology to address sanitation problems in peri-urban suburbs of Harare, Zimbabwe. These suburbs with an estimated population of 156.975 are unique in that they are not connected to the Harare main water sewer system. A baseline survey was conducted to determine the quantity of biodegradable human and kitchen waste (N=60). Biodigester sizing and costing was done for various scenarios mainly household standalone, single centralised suburb and combined suburbs centralised biogas models. In addition potential biogas conversion to electricity was done for single centralised suburb and combined suburbs centralised biogas models. This was followed by a cost benefit analysis of employing combined suburbs biogas technology. A combined suburbs centralised biogas model was found to be the most feasible scenario producing 7378 m3 of biogas per day with electricity production capacity of 384 kW.There was a potential of wood savings of 6129 tonnes/year, paraffin savings of 2.556 tonnes/year and greenhouse benefits of 980 tonnes of CO2 equivalent emissions/ year and which would attract U$2940 from carbon credits sales per year. The study recommended the adoption of the biogas technology because of its potential toaddress both economic and sanitation challenges being faced by local authorities in developing countries particularly, improved hygienic conditions, energy supply chronic epidemics and sewer reticulation.